Selective inhibition of COX-2 in humans is associated with less gastrointestinal injury: a comparison of nimesulide and naproxen. Issue 3 (1st March 2001) - Shah, A A; Thjodleifsson, B; Murray, F E; Kay, E; Barry, M; Sigthorsson, G; Gudjonsson, H; Oddsson, E; Price, A B; Fitzgerald, D J; Bjarnason, I
Abstract : BACKGROUND: Selective inhibitors of cyclooxygenase (COX)-2 may provoke less gastric damage and platelet inhibition than conventional non-steroidal anti-inflammatory drugs. AIMS: We compared the biochemical and gastrointestinal effects of nimesulide, a potent and selective COX-2 inhibitor, with naproxen which exhibits no selectivity. SUBJECTS: Thirty six healthy volunteers were randomised to nimesulide 100 mg or naproxen 500 mg twice daily for two weeks in a double blind, crossover study with a washout between treatments. METHODS: Gastrointestinal side effects were assessed by endoscopy, and by estimation of small intestinal absorption-permeability and inflammation. Comparisons were made between variables at the end of each treatment phase. RESULTS: Nimesulide caused significantly less gastric injury using the modified Lanza score (p<0.001) as well as reduced duodenum injury (p=0.039). Nimesulide had lower visual analogue scores (VAS) for haemorrhage and erosive lesions in the stomach (p<0.001) and for mucosal injection in the duodenum (p=0.039). Naproxen increased excretion of calprotectin, a marker of intestinal inflammation (5.5 (1.2) to 12.1 (2.1) mg/l) while nimesulide had no effect (treatment difference p=0.03). Naproxen abolished platelet aggregation to arachidonic acid and suppressed serum thromboxane B2 (TXB2 ) by 98%, indices of COX-1 activity. In contrast, nimesulide had no significant effect on platelet aggregation, although it reduced serum TXB2 by 29%. Production of prostaglandin E2 and prostacyclin by gastric biopsies, also COX-1 dependent, was inhibited by naproxen, but not by nimesulide. COX-2 activity, determined as endotoxin induced prostaglandin E2 formation in plasma, was markedly suppressed by both treatments. INTERPRETATION: Nimesulide has preferential selectivity for COX-2 over COX-1 in vivo at full therapeutic doses and induces less gastrointestinal damage than that seen with naproxen in the short term.